Purification and characterization of a Bacillus subtilis keratinase and its prospective application in feed industry - Gupta, Sonali; Nigam, Arti; Singh, Rajni (Acta Biologica Szegediensis, 2015)
We have isolated a Bacillus subtilis strain (RSE163) from soil and explored for keratinase production. Keratinase was purified using chromatographic methods (Sephadex G-75 and Q Sepharose) resulting in 8.42-fold purification with 3303 U/mg specific activity.The purified enzyme displayed 3 bands in close proximity between 20 to 22 kDa in SDS-PAGE which were apparent to the zone of hydrolysis in gelatin zymogram. Enzyme was stable over a wide pH (7.0-10.0) and temperature (30 °C to 70 °C) range with optimum activity at pH 9.0 and 60 °C. Keratinase activity was stimulated in presence of Mn2+, β-mercaptoethanol and surfactants (Triton-X and Tween-80) and inhibited by Fe3+, Cd2+, K+, PMSF (phenyl methane sulfonyl fluoride) and other chelating and reducing agents. The enzyme efficiently hydrolyzed a variety of complex protein substrates (chicken feather, keratin hydrolyzate and casein) and enzyme kinetics parameters were determined using Lineweaver Burk plot (Km = 6.6 mg/ml, Vmax = 5 U/ml/min). Hydrolyzed feather keratin obtained through fermentation with B. subtilis RSE163 has been explored for its cytotoxicity using liver cell line (HepG2). No cytotoxicity has been determined up to 0.015% concentration of hydrolyzed product indicating its potential applicability as feed supplement.